New records of phytoplankton for Bangladesh. 2. Cryptophyceae and Synurophyceae - Khondker, Moniruzzaman; Bhuiyan, Rauf Ahmed; Yeasmin, Jenat; Alam, Munirul; Sack, R Bradley; Huq, Anwar; Colwell, Rita R (Bangladesh Journal of Botany, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> This study presents two species of Rhodomonas, four species of Chroomonas, six species of Cryptomonas and Cryptochrysis minor, Cyanomonas coeruleus, Chrysodidymus synuroideus and Mallomonas akrokomos. These species have been reported from some ponds of Mathbaria in Pirojpur and Bakerganj of Barisal district in Bangladesh. Â  Key words: Phytoplankton, New records, Cryptomonads, Synuroids, Ponds doi:10.3329/bjb.v36i1.1549 Bangladesh J. Bot. 36(1): 53-59, 2007 (June)